2021
DOI: 10.3390/molecules26237408
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Chiral Ligands of Bis(imidazolinyl)- and Bis(oxazolinyl)thiophenes—Synthesis and Application in Cu-Catalyzed Friedel–Crafts Asymmetric Alkylation

Abstract: Five new C2-symmetric chiral ligands of 2,5-bis(imidazolinyl)thiophene (L1–L3) and 2,5-bis(oxazolinyl)thiophene (L4 and L5) were synthesized from thiophene-2,5-dicarboxylic acid (1) with enantiopure amino alcohols (4a–c) in excellent optical purity and chemical yield. The utility of these new chiral ligands for Friedel–Crafts asymmetric alkylation was explored. Subsequently, the optimized tridentate ligand L5 and Cu(OTf)2 catalyst (15 mol%) in toluene for 48 h promoted Friedel–Crafts asymmetric alkylation in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…A plausible reaction pathway was suggested, indicating that the deep chiral pocket serving as a confined reaction space stabilizes β-disubstituted nitroalkene 94 through noncovalent interactions and favoring the attack of an incoming indole nucleophile from the Re -face of the β-disubstituted nitroalkene to afford the corresponding alkylated product in R -configuration. In 2021, Al-Majid et al reported the synthesis of chiral 2,5-bis­(oxazolinyl)­thiophene ligands and studied their utility in the asymmetric F–C reaction of indoles 96 with β-nitroolefins 97 . The methodology employs 15 mol % of the Cu­(OTf) 2 / L28 complex catalyst system to provide access to the corresponding functionalized indoles 98 in low to moderate yields and poor to good enantiomeric excess (up to 81% ee; Scheme b).…”
Section: Conjugate Addition To Electrophilic Cc Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…A plausible reaction pathway was suggested, indicating that the deep chiral pocket serving as a confined reaction space stabilizes β-disubstituted nitroalkene 94 through noncovalent interactions and favoring the attack of an incoming indole nucleophile from the Re -face of the β-disubstituted nitroalkene to afford the corresponding alkylated product in R -configuration. In 2021, Al-Majid et al reported the synthesis of chiral 2,5-bis­(oxazolinyl)­thiophene ligands and studied their utility in the asymmetric F–C reaction of indoles 96 with β-nitroolefins 97 . The methodology employs 15 mol % of the Cu­(OTf) 2 / L28 complex catalyst system to provide access to the corresponding functionalized indoles 98 in low to moderate yields and poor to good enantiomeric excess (up to 81% ee; Scheme b).…”
Section: Conjugate Addition To Electrophilic Cc Bondsmentioning
confidence: 99%
“…In 2021, Al-Majid et al reported the synthesis of chiral 2,5-bis(oxazolinyl)thiophene ligands and studied their utility in the asymmetric F–C reaction of indoles 96 with β-nitroolefins 97 . 52 The methodology employs 15 mol % of the Cu(OTf) 2 / L28 complex catalyst system to provide access to the corresponding functionalized indoles 98 in low to moderate yields and poor to good enantiomeric excess (up to 81% ee; Scheme 19 b). A wide range of nitroolefins containing diverse substituents on the aryl ring, irrespective of electronic nature, were well-tolerated.…”
Section: Conjugate Addition To Electrophilic C=c Bondsmentioning
confidence: 99%
“…The N atom in the oxazoline ring contains lone pair electrons, which can form strong coordination bonds with metal ions and has broad spectrum metal coordination ability. In addition, chiral oxazoline and its metal complexes have been widely used in various types of asymmetric catalytic reactions, including the Diels–Alder reaction, 33 Crafts reaction, 34 Aldol reaction, 35 Henry reaction, 36 Nitrile silicification reaction, 37 etc . They exhibit excellent catalytic activity and stereoselective control ability in these reactions, so they have received extensive attention, especially for ligands containing chiral oxazoline rings.…”
Section: Introductionmentioning
confidence: 99%
“…The β-nitrostyrenes have been very recently added as platform molecules of electrophiles in the asymmetric Friedel–Crafts reaction with indoles to obtain a range of bioactive indole derivatives. 11,12 To evaluate new chiral tetradentate bimetallic Nar–2NO ligands, we first tested the efficiency of the chiral Nar–2NO/2Ni(OTf) 2 complex generated in situ in a model reaction of indole 4a and β-nitrostyrene 5a (Table 1). The ligands L1a–m synthesized above were screened (entries 1–13), and better results for product 6a (entry 1, 90% yield, 93% ee) were obtained with the “parent” ligand L1a .…”
mentioning
confidence: 99%
“…These results demonstrated that the rigid structure and high steric hindrance of the L1a –2Ni( ii ) complex could form a superior chiral environment, and it can serve as an efficient chiral catalyst in the field of asymmetric catalysis. The absolute configuration 12 of 6a was assigned to be S based on X-ray crystallographic analysis. Based on the same plausible mechanism analysis, the stereochemistry of the other products 6 was assigned by analogy.…”
mentioning
confidence: 99%